Strengthening TINA: Using Pugh Matrix and Kano Analysis to Improve Its Design Threshold and Performance Criteria - Almaden, Antoniette M.; Pantinople, James D.; Ferrer, Lovenia M.; Forrosuelo, Laizame L.; Bongcales, Anthony Dave C.; Bastida, Ralph Warren P.; Cabanlit, Cheradee Ann M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Amidst the pandemic, the Teknoy-Inquiry Assistant (TINA) system was created to accommodate student institution–related questions while following the restrictions implemented by the government. Due to the rushed design, users experience untimely response problems when using the service. The research aims to investigate and propose improvements to the TINA system for the sustainability of the service. The researchers focused on the turn-around time for the replies to the questions in the TINA system. To further justify the importance of addressing the turn-around time of replies, the researchers also investigated the meaningful relationship between student satisfaction and response time. The researchers addressed and resolved the reply time using Kano Analysis. The research also used purposive sampling, using researcher-made survey questionnaires to find the relationship between student satisfaction and the timeliness of replies. With the help of the Pearson correlation coefficient, the researcher found a positive correlation between student satisfaction and reply time, with a positive correlation value of 0.4090. Since a positive correlation is found between student satisfaction and reply time, improving the turn-around time of reply certainly increases student satisfaction. Therefore, to improve TINA, the researchers advocate implementing its Artificial Intelligence Chatbot version to improve reply time. The research is the first to contribute to the Field of Technology and University Services within the local context since it may give practical suggestions on properly creating an Inquiry Assistant System among regional universities.